Respuesta :
Answer: (a) -12y (b) -3x^2-x+28
Explanation: Sorry I need to go so I can't finish the explanation, hope this helps!!!
Answer:
a. -12y
b. -3x^2 - x + 28
Explanation:
a. The expression:
(-18x*2y)/(3x)
can be simplified computing the division, that is, dividing -18*2 by 3 (which is equal to -12) and dividing x*y by x (which is equal to y). Then, the result is -12y.
b. To simplify the expression:
(x-4)*(x-1) - 4*(x-3)*(x+2)
first, use the distributive property as follows:
(x-4)*(x-1) = x^2 - x - 4x + 4 = x^2 - 5x + 4
4*(x-3)*(x+2) = (4x - 12)*(x+2) = 4x^2 + 8x - 12x -24 = 4x^2 - 4x - 24
Then replace in the original expression:
x^2 - 5x + 4 - (4x^2 - 4x - 24) =
= x^2 - 5x + 4 - 4x^2 + 4x +24 =
= -3x^2 - x + 28